DESIGN OF A SUPERVISION AND CONTROL SYSTEM FOR A MEETING ROOM - González Ibarra , Enier; Rueda Olivero, Karla; Pérez Benítez, Arturo Alejandro; Monteavaro García, Niurka; Montejo Valdés, Pablo (Telemática, 2025)
The meeting room of the rector's office of the Universidad Tecnológica de la Habana “José Antonio Echeverría” (CUJAE) does not have an automated or supervised control of its operation. To solve this problem, an extensible supervision and control system is designed based on a web application, as part of which control systems are designed for the room's lighting fixtures and the door lock. To elaborate these control systems, two ESPDuino boards with ESP8266 microcontrollers are used to control the room devices, which communicate with the server where the web application is hosted using the WebSocket protocol. The web application implements a direct control system for the room's lighting fixtures. The conventional lock present in the salon is modified to be used additionally as an electronic lock and an RFID identification system is designed to control the entrance to the salon. All changes to the lights or the room lock are stored in a database on the server. Thanks to the design of the monitoring and control system, it becomes easy to add new functions such as controlling the salon computer and monitoring all connected devices.